A polyethylene film and a method for producing the same

CN123001289APending Publication Date: 2026-10-30GUANGDONG BAILICHUANG MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611127060.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]一是抗菌性能差,纯聚乙烯分子链无法抑制细菌和霉菌生长

Benefits of technology

[0030]如果纳米纤维膜过厚,会导致薄膜透明度下降。该质量比范围可使复合薄膜同时具备优异的抗菌和抗静电性能,又保持了聚乙烯膜原有的高拉伸强度、高断裂伸长率和良好的水汽阻隔性能。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a polyethylene film and a preparation method thereof, and belongs to the field of high polymer materials, and the steps comprise the following steps: using a mixture of trifluoroacetic acid and dimethyl carbonate as a solvent, dissolving chitosan quaternary ammonium salt and sulfonic acid doped polyaniline to obtain a spinning solution; electrospinning the spinning solution to obtain a nanofiber membrane; placing a layer of polyethylene film on each of the upper and lower surfaces of the nanofiber membrane, and hot-pressing the polyethylene films to obtain a polyethylene film. In the polyethylene film, chitosan has a certain antibacterial effect, chitosan quaternary ammonium salt has a broad-spectrum antibacterial property, can destroy the integrity of the bacterial cell membrane, and cause the death of bacteria due to the leakage of the bacterial content, and sulfonic acid doped polyaniline has good conductivity. The two materials are mixed and electrospun into a film, a continuous conductive network can be formed, and after the polyethylene film is hot-pressed into a polyethylene film, the static electricity accumulated on the surface of the film can be promptly conducted away, so that dust and impurities are avoided from being adsorbed by static electricity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a polyethylene film and its preparation method, belonging to the field of polymer materials. Background Technology

[0002] Polyethylene film, with its advantages of being lightweight, transparent, flexible, and resistant to chemical corrosion, is widely used in fresh food packaging and medical packaging. In fresh food packaging, polyethylene film is used for preserving fruits, vegetables, meat, and seafood, effectively reducing moisture loss and extending shelf life. In medical packaging, polyethylene film is used for the aseptic packaging of disposable syringes, infusion sets, surgical instruments, and other medical devices, serving as an important barrier to ensure medical safety.

[0003] However, existing polyethylene films have some drawbacks in these two application scenarios.

[0004] First, its antibacterial properties are poor; pure polyethylene molecular chains cannot inhibit the growth of bacteria and mold. In the field of medical packaging, polyethylene film cannot effectively block external bacterial contamination, and bacteria easily grow on the packaging surface, posing a risk of cross-infection, especially in bacteria-intensive environments such as hospitals. Existing technologies typically use antibacterial agents coated on the surface of polyethylene film to improve antibacterial properties, but these agents are prone to peeling off, have poor durability, and some pose safety hazards, potentially migrating into food or medical devices.

[0005] Secondly, it has poor antistatic properties. Polyethylene is a non-polar polymer material with a volume resistivity as high as 10 Ω·cm. 16 ~10 18 The surface of the polyethylene film, with a diameter of Ω·cm, readily accumulates static electricity. Static electricity causes dust and impurities to adhere to the film surface, affecting the packaging's appearance and cleanliness. For medical packaging, dust and impurities may carry bacteria, further increasing the risk of cross-infection. On high-speed packaging production lines, static electricity can cause film adhesion, misalignment, and breakage, severely impacting production efficiency and increasing the scrap rate. Furthermore, in certain flammable and explosive environments, electrostatic discharge can trigger fires and explosions. Current technologies typically improve antistatic properties by adding antistatic agents to the polyethylene matrix. However, antistatic agents easily migrate to the film surface, and their antistatic effect gradually decreases with prolonged use. Moreover, there is mutual interference between antistatic and antibacterial agents; antibacterial agents can disrupt the conductive network of the antistatic agent, and the antistatic agent can reduce the antibacterial effect of the antibacterial agent. Additionally, excessive amounts can affect the film's mechanical properties and transparency. Summary of the Invention

[0006] To overcome the shortcomings of the prior art, the present invention provides a polyethylene film and its preparation method, which takes into account both antibacterial and antistatic properties.

[0007] The technical solution adopted by this invention to solve its technical problem is: In a first aspect, this application provides a method for preparing a polyethylene film, the steps of which include: A spinning solution was obtained by dissolving chitosan quaternary ammonium salt and sulfonic acid-doped polyaniline in a mixture of trifluoroacetic acid and dimethyl carbonate as a solvent. The spinning solution is electrospun to obtain a nanofiber membrane; A polyethylene film is placed on each of the top and bottom surfaces of the nanofiber membrane, and then hot-pressed together to obtain the polyethylene film.

[0008] The polyethylene film preparation method provided in this application produces a three-layer sandwich composite structure, with a nanofiber membrane as the middle layer, which allows antibacterial and conductive components to be evenly distributed inside the film, thus solving the problems of poor antibacterial performance and poor antistatic performance.

[0009] Further, the mass ratio of solute to solvent in the spinning solution is 1:6~7; of the solute, by mass, 10 to 20 parts of chitosan quaternary ammonium salt and 5 to 15 parts of sulfonic acid-doped polyaniline are used; of the solvent, the volume ratio of trifluoroacetic acid to dimethyl carbonate is 7:3~8:2.

[0010] The solvent system utilizes the strong polarity of trifluoroacetic acid to ensure complete dissolution of chitosan quaternary ammonium salt, while dimethyl carbonate regulates the solvent evaporation rate and improves the solubility of sulfonic acid-doped polyaniline, thus avoiding fiber defects caused by incomplete dissolution or excessively rapid solvent evaporation during spinning.

[0011] Preferably, the mass ratio of the chitosan quaternary ammonium salt to the sulfonic acid-doped polyaniline is 3:2. The conjugated molecular chains of the sulfonic acid-doped polyaniline form a continuous conductive network, providing stable antistatic properties; the cationic groups of the chitosan quaternary ammonium salt are interspersed in the gaps of the conductive network, which neither disrupts the network continuity nor fails to fully expose the fiber surface to exert antibacterial effects.

[0012] Furthermore, the solute also contains polyethylene oxide, and the mass ratio of the polyethylene oxide to the chitosan quaternary ammonium salt is 1:15~50.

[0013] A small amount of polyethylene oxide can solve the problems of filament breakage and fiber discontinuity caused by the high molecular chain rigidity of chitosan quaternary ammonium salt and sulfonic acid-doped polyaniline mixed solutions. Insufficient polyethylene oxide dosage results in limited improvement in spinnability; excessive dosage will dilute the concentration of functional components and reduce antibacterial and antistatic effects.

[0014] Furthermore, the molecular weight of the polyethylene oxide is 800,000 to 1,200,000.

[0015] Furthermore, before the step of placing a polyethylene film on each of the upper and lower surfaces of the nanofiber membrane, there is a further step: coating both the upper and lower surfaces of the nanofiber membrane with a polyvinyl butyral solution, drying the polyvinyl butyral solution, and obtaining a polyvinyl butyral coating with a thickness of 1μm to 3μm on each of the upper and lower surfaces of the nanofiber membrane.

[0016] Furthermore, the concentration of the polyvinyl butyral solution is 5 wt%.

[0017] Furthermore, the requirement for drying the polyvinyl butyral solution is as follows: first, place it at room temperature for 5 minutes, then raise the temperature to 45°C and dry for 15 minutes.

[0018] Further, the preparation steps of the chitosan quaternary ammonium salt include: dissolving chitosan in acetic acid solution, adding 2,3-epoxypropyltrimethylammonium chloride, heating and reacting, and then precipitating with alcohol to obtain the chitosan quaternary ammonium salt.

[0019] The chitosan quaternary ammonium salt prepared in this step has a moderate degree of substitution, ensuring good water solubility for complete dissolution in mixed solvents while providing sufficient cationic antibacterial groups to exert excellent antibacterial effects. Simultaneously, the moderate degree of substitution matches the molecular chain polarity of the chitosan quaternary ammonium salt with that of sulfonic acid-doped polyaniline and polyethylene oxide, preventing aggregation or phase separation in the spinning solution and ensuring uniform distribution of functional components within the fiber.

[0020] Furthermore, the mass ratio of the chitosan to the 2,3-epoxypropyltrimethylammonium chloride is 3:4~5.

[0021] When the amount of 2,3-epoxypropyltrimethylammonium chloride is below this range, the number of quaternary ammonium salt groups on the chitosan molecular chain is insufficient, resulting in poor water solubility, low efficiency in preparing spinning solutions, and insufficient antibacterial activity. When the amount is above this range, the substitution is too high, easily leading to strong electrostatic interactions and flocculation with sulfonic acid-doped polyaniline, which is not conducive to preparing a uniform spinning solution. Although the flocculants can be removed by filtering the spinning solution, the raw material utilization rate is low. The chitosan quaternary ammonium salt prepared at this mass ratio has a uniform distribution of quaternary ammonium salt groups, ensuring both good water solubility and antibacterial properties, and exhibiting optimal compatibility with sulfonic acid-doped polyaniline, without affecting the formation of the conductive network.

[0022] In addition, when the spinning solution contains polyethylene oxide, this ratio can also ensure that a stable hydrogen bond is formed between the chitosan quaternary ammonium salt and polyethylene oxide, further improving the spinnability of the spinning solution.

[0023] Further, the preparation steps of the sulfonic acid-doped polyaniline include: dissolving aniline in hydrochloric acid solution, cooling in an ice-water bath, adding ammonium persulfate solution dropwise to react and obtain polyaniline; adding p-toluenesulfonic acid to the hydrochloric acid dispersion of polyaniline, stirring and mixing to react, then filtering, washing until the pH reaches 4-5, and drying to obtain the sulfonic acid-doped polyaniline.

[0024] Washing to pH 4-5, rather than neutral, is to retain some of the protonated polyaniline structure, forming a more continuous and denser conductive network, which significantly improves the antistatic properties of the film. The sulfonic acid-doped polyaniline prepared in this step has excellent solubility in a trifluoroacetic acid-dimethyl carbonate mixed solvent, and can form a stable and homogeneous spinning solution with chitosan quaternary ammonium salt and polyethylene oxide. The fibers obtained after electrospinning have uniform conductivity and long-lasting antistatic effect.

[0025] Furthermore, in the raw materials for preparing the sulfonic acid-doped polyaniline, by mass, the aniline is used in 5 to 15 parts, the ammonium persulfate in 8 to 18 parts, and the p-toluenesulfonic acid in 10 to 20 parts.

[0026] Furthermore, the requirements for electrospinning are: flow rate of 0.8 mL / h to 2.0 mL / h, voltage of 12 kV to 20 kV, and receiving distance of 12 cm to 20 cm. This flow rate ensures that the supply rate of the spinning solution matches the jet stretching rate of the spinning solution, preventing jet breakage due to excessively slow flow rate and avoiding excessively fast flow rate leading to excessively large fiber diameter or bead-like defects.

[0027] Furthermore, the hot-pressing composite conditions are: temperature 105℃~125℃, pressure 1MPa~3MPa, and time 2min~6min. This temperature allows the polyethylene film surface to soften slightly without causing excessive melting and deformation or uneven thickness, and it also does not damage the structure and activity of the nanofibers' functional components.

[0028] Furthermore, ultrasonic assistance is applied during the hot-pressing process, with a power of 200W~400W and a frequency of 20kHz~40kHz. The mechanical vibration of the ultrasound can make the temperature and pressure distribution more uniform during the hot-pressing process, avoiding film deformation, uneven thickness, and performance differences caused by local overheating or uneven pressure. With ultrasonic assistance, better interfacial bonding can be achieved at lower temperatures and pressures, reducing the adverse effects of high temperature and high pressure on film performance, while shortening the hot-pressing time and improving production efficiency.

[0029] Furthermore, in the hot-pressing composite step, the ratio of the total thickness of the two polyethylene films to the thickness of the nanofiber film is 3~4:10.

[0030] If the nanofiber membrane is too thick, it will lead to a decrease in film transparency. This mass ratio range allows the composite film to simultaneously possess excellent antibacterial and antistatic properties, while maintaining the original high tensile strength, high elongation at break, and good water vapor barrier properties of the polyethylene film.

[0031] Secondly, this application provides a polyethylene film made by the polyethylene film preparation method described in the first aspect.

[0032] The beneficial effects of this invention are: chitosan itself has a certain antibacterial effect, and chitosan quaternary ammonium salt has a broader spectrum of antibacterial properties, which can destroy the integrity of bacterial cell membranes, causing bacterial contents to leak out and die. Sulfonic acid-doped polyaniline has good conductivity. When these two materials are mixed and electrospun into a film, a continuous conductive network can be formed. After being hot-pressed with polyethylene into a polyethylene film, the static electricity accumulated on the surface of the film can be conducted away in time, avoiding the static adsorption of dust and impurities. Detailed Implementation

[0033] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions of the embodiments of this disclosure are described clearly and completely below. Obviously, the described embodiments are only some, not all, of the embodiments of this disclosure. All other embodiments obtained by those skilled in the art based on the described embodiments of this disclosure without creative effort are within the scope of protection of this invention.

[0034] It should be understood that, without conflict, any and all embodiments of the present invention can be combined with technical features of any other embodiment or multiple other embodiments to obtain other embodiments. The present invention includes such combinations to obtain other embodiments.

[0035] In this specification, groups and their substituents may be selected by those skilled in the art to provide stable structural moieties and compounds. When a substituent is described by a conventional chemical formula written from left to right, the substituent also includes chemically equivalent substituents obtained when the structural formula is written from right to left.

[0036] Unless otherwise specified, all technical and scientific terms used herein have the standard meaning in the field to which the claimed subject matter pertains. Where multiple definitions exist for a term, the definition herein shall prevail.

[0037] This application provides a method for preparing a polyethylene film, the steps of which include: S1: Using a mixture of trifluoroacetic acid and dimethyl carbonate as a solvent, chitosan quaternary ammonium salt and sulfonic acid-doped polyaniline are dissolved to obtain a spinning solution.

[0038] S2: Electrospin the spinning solution to obtain a nanofiber membrane.

[0039] S3: Place a layer of polyethylene film on each of the top and bottom surfaces of the nanofiber membrane, and then hot-press them together to obtain a polyethylene film.

[0040] This application addresses the core pain points of existing technologies, such as mutual interference, easy migration, and poor durability of antibacterial and antistatic agents. A mixed solvent composed of trifluoroacetic acid and dimethyl carbonate can simultaneously dissolve chitosan quaternary ammonium salt and sulfonic acid-doped polyaniline, which have significantly different polarities. This allows the two functional components to form a molecularly homogeneous dispersion system in the spinning solution, avoiding agglomeration during direct blending. The electrospinning process transforms the mixed solution into continuous fibers with a diameter of hundreds of nanometers, greatly increasing the specific surface area of ​​the functional components. This allows the antibacterial groups and conductive units to function effectively without migrating to the surface. Because the two functional components are pre-fixed within the nanofibers, there is no issue of free migration within the matrix. Therefore, the mutual interference phenomena of antibacterial agents damaging the conductive network of antistatic agents and antistatic agents inhibiting antibacterial activity are avoided. Furthermore, the light scattering effect of nanofibers is weak, minimizing its impact on film transparency.

[0041] Both chitosan quaternary ammonium salt and sulfonic acid-doped polyaniline can be commercially available raw materials, and the polyethylene film can be a commercially available finished film or blown from PE plastic granules. Preferably, chitosan quaternary ammonium salt and sulfonic acid-doped polyaniline, which are more suitable for electrospinning by mixing the two, can also be prepared in-house.

[0042] For example, the preparation steps of sulfonic acid-doped conductive polyaniline (sulfonic acid-doped polyaniline) are as follows: aniline is dissolved in hydrochloric acid solution, ammonium persulfate is added as an initiator, and the reaction is carried out at 0-5℃ for 6-12 hours to obtain polyaniline. Then, it is doped with p-toluenesulfonic acid, washed until the pH is 4-5, and vacuum dried to obtain sulfonic acid-doped conductive polyaniline. Raw material amounts: 5-15 parts aniline, 100-200 parts hydrochloric acid solution, 8-18 parts ammonium persulfate, and 10-20 parts p-toluenesulfonic acid.

[0043] The preparation steps of chitosan quaternary ammonium salt are as follows: Chitosan is dissolved in acetic acid solution, 2,3-epoxypropyltrimethylammonium chloride is added, the mixture is heated and reacted, and then precipitated with alcohol to obtain chitosan quaternary ammonium salt. The mass ratio of chitosan to 2,3-epoxypropyltrimethylammonium chloride is 3:4~5.

[0044] Step S1 specifically involves dissolving quaternary ammonium salt modified chitosan (chitosan quaternary ammonium salt) and sulfonic acid-doped conductive polyaniline in a mixed solvent of trifluoroacetic acid and dimethyl carbonate (volume ratio 7:3~8:2), and stirring until homogeneous to obtain a spinning solution. Raw material amounts: 10~20 parts quaternary ammonium salt modified chitosan, 5~15 parts sulfonic acid-doped conductive polyaniline, and 100~200 parts mixed solvent.

[0045] Step S2 specifically involves preparing nanofiber membranes using electrospinning technology. Spinning parameters: flow rate 0.8~2.0 mL / h, voltage 12~20 kV, receiving distance 12~20 cm, ambient temperature 20~30℃, ambient humidity 30%~50%.

[0046] Step S3 specifically involves placing two layers of polyethylene film on the upper and lower sides of the nanofiber film, respectively, and then hot-pressing them together on a hot press while applying ultrasonic assistance. Hot-pressing parameters: temperature 105~125℃, pressure 1~3MPa, time 2~6 minutes; ultrasonic parameters: power 200~400W, frequency 20~40kHz. Raw material usage: 85~95 parts polyethylene film, 5~15 parts nanofiber film.

[0047] Toluenesulfonic acid was chosen for doping polyaniline because its sulfonic acid groups can protonate the imino groups on the polyaniline molecular chain, improving its conductivity and environmental stability, allowing it to maintain good conductivity even in humid and high-temperature environments. Washing to a pH of 4-5 (not neutral) preserves sufficient protonation sites on the polyaniline molecular chain, preventing deprotonation and subsequent conductivity degradation. The strong acidity of trifluoroacetic acid maintains an acidic environment, preventing deprotonation of the polyaniline, while dimethyl carbonate regulates solvent volatility and improves the stability of the electrospinning process. Electrospinning a blend of quaternary ammonium salt-modified chitosan and sulfonic acid-doped conductive polyaniline allows for the uniform distribution of antibacterial and conductive components within the nanofibers. During ultrasonic-assisted hot-pressing, the cavitation effect and mechanical vibration generated by the ultrasound promote the penetration of polyethylene molecular chains into the nanofiber membrane, enhancing interlayer bonding, while simultaneously reducing hot-pressing temperature and pressure, minimizing damage to the nanofiber structure.

[0048] Preferably, before electrospinning, the prepared spinning solution is placed in a vacuum drying oven and degassed at room temperature for 30 minutes to remove air bubbles from the spinning solution. This can prevent fiber breakage or bead-like defects caused by air bubble rupture during the spinning process, thereby improving fiber continuity and uniformity.

[0049] Preferably, after degassing, the spinning solution is filtered through a 200-mesh stainless steel filter to remove incompletely dissolved microparticles and impurities from the spinning solution, preventing clogging of the spinning needles and further improving the continuity and uniformity of the fibers.

[0050] Preferably, after hot pressing and lamination, the composite film is annealed in a 60°C oven for 2 hours to eliminate residual stress inside the composite film, improve dimensional stability, and reduce warping deformation during use.

[0051] In the above embodiments, the concentrations of quaternary ammonium salt-modified chitosan and sulfonic acid-doped conductive polyaniline are relatively high, which can lead to slight instability in the spinning process, resulting in uneven fiber diameter and even fiber breakage, thus affecting the electrospinning efficiency. To address this issue, during the preparation of the spinning solution, quaternary ammonium salt-modified chitosan is first added to the mixed solvent and dissolved using ultrasound at 40-50°C for 1-2 hours. After complete dissolution, sulfonic acid-doped conductive polyaniline is then added, and the solution is dissolved using ultrasound at 40-50°C for another 1-2 hours. Simultaneously, polyethylene oxide is added to the spinning solution at a low content (mass ratio of polyethylene oxide to chitosan quaternary ammonium salt is 1:15-50) as a spinning aid polymer. After thorough stirring, electrospinning is performed.

[0052] The combination of stepwise dissolution and ultrasonic-assisted dissolution can shorten the dissolution time from 24 hours to 4-6 hours, significantly improving production efficiency and avoiding the degradation of polyaniline molecular chains caused by prolonged mechanical stirring, thus maintaining the electrical conductivity of polyaniline. The molecular chains of polyethylene oxide possess excellent flexibility and fiber-forming properties, effectively regulating the rheological properties of the spinning solution, reducing the viscosity of high-concentration spinning solutions, improving the spinnability of the spinning solution, and making the spinning process more stable. Simultaneously, the ether bonds in the polyethylene oxide molecular chains can absorb moisture from the air, forming a continuous water film on the fiber surface, providing additional ion-conducting channels and further enhancing the antistatic properties of the composite film.

[0053] Preferably, polyethylene oxide with a molecular weight of 800,000 to 1,200,000 is selected as the spinning aid polymer. Polyethylene oxide in this molecular weight range can effectively improve the spinnability of the spinning solution without causing excessive viscosity due to excessive molecular weight, while maintaining good antistatic effect.

[0054] Due to the presence of the nanofiber membrane, light is scattered to a certain extent, resulting in a 5%–10% lower light transmittance compared to pure polyethylene film. For packaging applications requiring high transparency, such as high-end fresh food packaging and pharmaceutical packaging, there is still room for improvement. To address this issue, a 1–3 μm thick polyvinyl butyral coating is applied to both the top and bottom sides of the nanofiber membrane before hot-pressing. The coating is done using a blade coating method at a speed of 0.5–1.0 m / min, followed by drying at 40–50°C for 10–20 minutes. Ultrasonic-assisted hot-pressing is then performed.

[0055] Polyvinyl butyral (PVB) exhibits excellent transparency and adhesion. Its refractive index is similar to that of polyethylene and nanofiber membranes, reducing light scattering at the interface and improving the transmittance of the composite film, approaching that of pure polyethylene films. Simultaneously, the PVB coating fills the micropores and uneven areas on the surface of the nanofiber membrane, improving its surface smoothness. Furthermore, PVB has a wide melting temperature range, which broadens the heat-sealing temperature range of the composite film.

[0056] Preferably, a 5% polyvinyl butyral ethanol solution is used for coating. This concentration ensures a uniform and continuous coating without being too thick and affecting light transmittance due to excessive concentration, or too incomplete and ineffective due to insufficient concentration.

[0057] Preferably, after coating, the coating is left at room temperature for 5 minutes, then heated to 45°C and dried for 15 minutes. This drying method avoids rapid solvent evaporation that could cause pinholes and cracks in the coating, ensuring the integrity and density of the coating.

[0058] In the following comparative examples and embodiments, the polyethylene film was obtained by blowing film from Dow 2750ST plastic pellets, and all other reagents were of analytical grade unless otherwise specified. Example 1

[0059] Preparation of spinning solution: 15 parts of quaternary ammonium salt modified chitosan (MS0818, Shanghai Maokang Biotechnology Co., Ltd.) and 10 parts of sulfonic acid group doped conductive polyaniline (PA78519, Bofei Meco) were added to 150 parts of trifluoroacetic acid / dimethyl carbonate mixed solvent (volume ratio 7.5:2.5) and stirred at room temperature for 24 hours to obtain spinning solution.

[0060] Electrospinning: The spinning solution was loaded into a 10mL syringe, fitted with a No. 21 stainless steel needle, and electrospinning was performed using a flat receiving device. Spinning parameters were set as follows: flow rate 1.2mL / h, voltage 16kV, receiving distance 16cm, ambient temperature 25℃, and ambient humidity 40%. After spinning, the received nanofiber membrane was placed in a vacuum drying oven and dried at 40℃ for 6 hours to remove residual solvent, yielding a nanofiber membrane approximately 35μm thick.

[0061] Ultrasonic-assisted hot-press lamination: The nanofiber membrane is cut to the same size as the polyethylene membrane. Two 0.05mm thick polyethylene films are placed on the top and bottom sides of the nanofiber membrane, respectively. The three-layer structure is placed in a hot press, and the ultrasonic device is turned on simultaneously. The hot-press parameters are set as follows: temperature 115℃, pressure 2MPa, time 4 minutes; ultrasonic parameters: power 300W, frequency 30kHz. After hot pressing, the composite film is removed and allowed to cool naturally to room temperature to obtain the final product. Example 2

[0062] It is largely the same as Example 1, except that the chitosan quaternary ammonium salt and sulfonic acid-doped polyaniline are homemade.

[0063] Preparation of quaternary ammonium salt modified chitosan: 15 parts of chitosan (Sinopharm Group, degree of deacetylation ≥90%) were dissolved in 150 parts of 2% acetic acid solution and stirred until completely dissolved. 22 parts of 2,3-epoxypropyltrimethylammonium chloride were added, and the mixture was stirred in a 50℃ water bath for 6 hours. After the reaction was completed, the product was precipitated with anhydrous ethanol, washed three times with anhydrous ethanol, and dried in a 60℃ vacuum drying oven for 12 hours to obtain quaternary ammonium salt modified chitosan.

[0064] Preparation of sulfonic acid-doped conductive polyaniline: 10 parts of aniline were dissolved in 150 parts of 1 mol / L hydrochloric acid solution, stirred until homogeneous, and cooled in an ice-water bath at 0℃ for 30 minutes. 13 parts of ammonium persulfate were dissolved in 50 parts of deionized water and slowly added dropwise to the aniline solution over 30 minutes. After the addition was complete, the reaction was continued at 0-5℃ for 9 hours. After the reaction was completed, the polyaniline was obtained by filtration, washed three times with 1 mol / L hydrochloric acid solution, and then 15 parts of p-toluenesulfonic acid were added. The mixture was stirred and doped at room temperature for 4 hours, filtered, washed with deionized water until the pH reached 4-5, and dried in a vacuum drying oven at 60℃ for 12 hours to obtain sulfonic acid-doped conductive polyaniline. Example 3

[0065] It is largely the same as Example 2, except that the spinning solution composition is different.

[0066] Preparation of spinning solution: 8 parts of quaternary ammonium salt modified chitosan (prepared as in Example 2) and 18 parts of sulfonic acid group doped conductive polyaniline (prepared as in Example 2) were added to 160 parts of trifluoroacetic acid / dimethyl carbonate mixed solvent (volume ratio 6.5:3.5) and stirred at room temperature for 24 hours to obtain spinning solution. Example 4

[0067] It is largely the same as Example 2, except that the spinning solution composition is different.

[0068] Preparation of spinning solution: 15 parts of quaternary ammonium salt modified chitosan (prepared as in Example 2) were added to 150 parts of a trifluoroacetic acid / dimethyl carbonate mixed solvent (volume ratio 7.5:2.5). The solution was dissolved using ultrasound at 45°C for 1.5 hours until completely dissolved. Then, 10 parts of sulfonic acid-doped conductive polyaniline (prepared as in Example 2) were added, and the solution was dissolved using ultrasound at 45°C for another 1.5 hours. Next, 0.6 parts of polyethylene oxide (molecular weight 1 million, Aladdin product number P101344) were added, and the mixture was stirred for 2 hours until completely dissolved. The prepared spinning solution was placed in a vacuum drying oven and degassed at room temperature for 30 minutes to remove air bubbles. Example 5

[0069] Similar to Example 4, the difference lies in the preparation of a polyvinyl butyral coating before hot-pressing lamination: 3 parts of polyvinyl butyral (BM-S, Sekisui, Japan) were dissolved in 97 parts of anhydrous ethanol and stirred until completely dissolved to obtain a 3% polyvinyl butyral solution. This solution was then uniformly coated onto the upper and lower sides of the nanofiber membrane using a blade coating method, controlling the coating thickness to 2 μm at a coating speed of 0.8 m / min. After coating, the nanofiber membrane was placed in a 45°C oven for 15 minutes to dry and remove the anhydrous ethanol solvent.

[0070] Ultrasonic-assisted hot-press lamination: The coated nanofiber membrane is cut to the same size as the polyethylene film. Two 0.05mm thick polyethylene films are placed on the top and bottom sides of the nanofiber membrane, respectively. The three-layer structure is placed in a hot press, and the ultrasonic device is turned on simultaneously. The hot-press parameters are set as follows: temperature 115℃, pressure 2MPa, time 4 minutes; ultrasonic parameters: power 300W, frequency 30kHz. After hot pressing, the composite film is removed and allowed to cool naturally to room temperature to obtain the final product. Example 6

[0071] Similar to Example 5, the difference lies in the specific steps for preparing the polyvinyl butyral coating: 5 parts of polyvinyl butyral (BM-S, Sekisui, Japan) were dissolved in 95 parts of anhydrous ethanol and stirred until completely dissolved to obtain a 5% polyvinyl butyral solution. This solution was then uniformly coated onto the upper and lower sides of the nanofiber membrane using a blade coating method, controlling the coating thickness to 2 μm at a coating speed of 0.8 m / min. The membrane was first left at room temperature for 5 minutes, then heated to 45°C and dried for 15 minutes. Example 7

[0072] It is largely the same as Example 2, except that the single-layer thickness of the polyethylene film used as raw material during hot-pressing is 70 μm. Example 8

[0073] The process is largely the same as in Example 2, except that there is no ultrasonic assistance during hot pressing: hot pressing temperature 135°C, pressure 4MPa, time 5min.

[0074] Comparative Example 1 A PE plastic film with a thickness of 100μm was obtained by directly blowing film using Dow 2750ST plastic pellets.

[0075] Comparative Example 2 Compared with Comparative Example 1, the difference is that the blown film raw material also contains 2% antistatic agent (Ionphase PE0108M) and 2% antibacterial agent (silver zirconium phosphate).

[0076] The following tests were performed on each embodiment and comparative example, and the test results are shown in Table 1.

[0077] Antibacterial performance test: According to GB / T21510-2024 "Test Method for Antibacterial Performance of Nano-Inorganic Materials", the 24-hour antibacterial rate of the sample against Escherichia coli and Staphylococcus aureus was tested. Accelerated aging test was also conducted: the sample was placed in an environment of 60℃ and 90% relative humidity for 30 days, and the antibacterial rate of the two bacteria was tested again to evaluate the antibacterial durability.

[0078] Antistatic performance testing: The surface resistivity of the samples was tested using a high-resistivity meter according to GB / T 31838.2-2019 "Test Methods for Volume Resistivity and Surface Resistivity of Solid Insulating Materials". Accelerated aging tests were also performed to evaluate antistatic durability.

[0079] Optical performance testing: In accordance with GB / T2410-2008 "Determination of transmittance and haze of transparent plastics", the transmittance and haze of the samples were tested at a wavelength of 550 nm using a UV-Vis spectrophotometer.

[0080] Heat sealing performance test: According to QB / T2358-1998 "Test method for heat sealing strength of plastic film packaging bags", the heat sealing strength is tested by heat sealing at 115℃ and 0.2MPa pressure for 1s using a heat sealing machine.

[0081] Table 1 Escherichia coli antibacterial rate (%) 97.2 99.2 92.5 99.3 99.3 99.4 96.1 98.5 - 85.6 Staphylococcus aureus antibacterial rate (%) 96.8 99.1 91.7 99.2 99.2 99.3 94.9 98.3 - 83.2 Antibacterial rate of aged Escherichia coli (%) 89.5 94.3 82.1 95.1 95.0 95.2 88.6 93.0 - 52.7 Antibacterial rate of Staphylococcus aureus after aging (%) 88.7 93.8 81.3 94.6 94.5 94.8 87.9 92.4 - 48.3 Surface resistivity (Ω・cm) <![CDATA[1.2×10 9 ]]> <![CDATA[8.2×10 8 ]]> <![CDATA[3.6×10 8 ]]> <![CDATA[6.5×10 7 ]]> <![CDATA[6.3×10 7 ]]> <![CDATA[5.8×10 7 ]]> <![CDATA[2.3×10 9 ]]> <![CDATA[1.9×10 9 ]]> <![CDATA[2.1×10 11 ]]> <![CDATA[2.0×10 9 ]]> Surface resistivity after aging (Ω・cm) <![CDATA[3.5×10 9 ]]> <![CDATA[2.1×10 9 ]]> <![CDATA[9.8×10 8 ]]> <![CDATA[1.8×10 8 ]]> <![CDATA[1.7×10 8 ]]> <![CDATA[1.5×10 8 ]]> <![CDATA[6.7×10 9 ]]> <![CDATA[4.2×10 9 ]]> <![CDATA[2.0×10 11 ]]> <![CDATA[7.8×10 10 ]]> Light transmittance (%) 83.6 84.2 82.8 83.5 87.6 90.7 78.5 83.1 91.5 86.3 Haze (%) 7.8 7.2 8.5 7.5 4.8 2.9 10.2 7.9 2.5 5.1 Heat seal strength at 115℃ (N / cm) 3.8 4.0 3.6 4.2 4.8 5.5 4.1 3.2 3.9 3.7 While the traditional additive method (Comparative Example 2) achieved an initial antibacterial rate of over 80%, the rate decreased significantly after aging. This is likely because the antibacterial agent, which acts as a filler, has poor compatibility with the polyethylene matrix, causing it to migrate and be lost to the surface via diffusion. In all embodiments of this invention, the initial antibacterial rate was ≥91.7%, and the antibacterial rate after aging remained ≥81.3%, far superior to Comparative Example 2. The core reason is that both chitosan quaternary ammonium salt and sulfonic acid-doped polyaniline are high molecular weight compounds that cannot freely migrate and be lost. Example 3 showed an initial and aged antibacterial rate approximately 7 percentage points lower than Example 2, demonstrating that the functional component ratio directly determines the antibacterial effect.

[0082] In all embodiments of the present invention, the initial surface resistivity meets industrial antistatic standards. In Examples 4 to 6, the surface resistivity further decreased to 10 after the addition of polyethylene oxide. 7 It is on the order of Ω·cm, and its sexual function decreases with age.

[0083] The high resistivity in Example 8 may be due to excessively high hot-pressing temperature causing some nanofibers to melt and break, thus damaging the conductive network.

[0084] Pure PE film has the highest light transmittance (91.5%) and the lowest haze (2.5%), but lacks any functional properties. In Example 6 of this invention, a 5% concentration PVB coating combined with a gradient drying process achieves light transmittance and haze levels approaching those of pure PE film.

[0085] Compared to Example 5, Example 6 showed improved light transmittance and reduced haze, demonstrating that the PVB coating concentration and drying process are crucial to optical performance.

[0086] The heat seal strength at 115℃ in all embodiments of the present invention is ≥3.2N / cm, which meets the requirements for packaging use.

[0087] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, material, or characteristic described in connection with the embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0088] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a polyethylene film, characterized in that the steps include... include: A spinning solution was obtained by dissolving chitosan quaternary ammonium salt and sulfonic acid-doped polyaniline in a mixture of trifluoroacetic acid and dimethyl carbonate as a solvent. The spinning solution is electrospun to obtain a nanofiber membrane; A polyethylene film is placed on each of the top and bottom surfaces of the nanofiber membrane, and then hot-pressed together to obtain the polyethylene film.

2. The method for preparing polyethylene film according to claim 1, characterized in that, The mass ratio of solute to solvent in the spinning solution is 1:6~7; of the solute, by mass, the chitosan quaternary ammonium salt is 10 parts to 20 parts, and the sulfonic acid-doped polyaniline is 5 parts to 15 parts; of the solvent, the volume ratio of trifluoroacetic acid to dimethyl carbonate is 7:3~8:

2.

3. The method for preparing polyethylene film according to claim 2, characterized in that, The solute also contains polyethylene oxide, and the mass ratio of the polyethylene oxide to the chitosan quaternary ammonium salt is 1:15~50.

4. The method for preparing polyethylene film according to claim 3, characterized in that, The molecular weight of the polyethylene oxide is 800,000 to 1,200,000.

5. The method for preparing polyethylene film according to claim 1, characterized in that, Before the step of placing a polyethylene film on each of the upper and lower surfaces of the nanofiber membrane, there is another step: A polyvinyl butyral solution is coated on both the upper and lower surfaces of the nanofiber membrane. The polyvinyl butyral solution is then dried, resulting in a polyvinyl butyral coating with a thickness of 1 μm to 3 μm on each of the upper and lower surfaces of the nanofiber membrane.

6. The method for preparing polyethylene film according to claim 5, characterized in that, The concentration of the polyvinyl butyral solution is 5 wt%.

7. The method for preparing polyethylene film according to claim 5, characterized in that, The requirements for drying the polyvinyl butyral solution are as follows: first, place it at room temperature for 5 minutes, then raise the temperature to 45°C and dry for 15 minutes.

8. The method for preparing polyethylene film according to claim 1, characterized in that, The preparation steps of the chitosan quaternary ammonium salt include: dissolving chitosan in acetic acid solution, adding 2,3-epoxypropyltrimethylammonium chloride, heating and reacting, and then precipitating with alcohol to obtain the chitosan quaternary ammonium salt.

9. The method for preparing polyethylene film according to claim 1, characterized in that, The preparation steps of the sulfonic acid-doped polyaniline include: dissolving aniline in hydrochloric acid solution, cooling in an ice-water bath, adding ammonium persulfate solution dropwise to react and obtain polyaniline; adding p-toluenesulfonic acid to the hydrochloric acid dispersion of polyaniline, stirring and mixing to react, then filtering, washing until the pH reaches 4-5, and drying to obtain the sulfonic acid-doped polyaniline.

10. A polyethylene film, characterized in that, It is made by the polyethylene film preparation method according to any one of claims 1 to 9.